Synthesis and In Vitro Activity of Pyrrolo[3,4-d]pyrimidine-2,5-diones as Potential Non-nucleoside HCV Inhibitors - S. Mostafa, Amany; A. El Bialy, Serry; A. Bayoumi, Waleed; Ueda, Youki; Ikeda, Masanori; Kato, Nobuyuki; M. Abdelal, Ali (Current Enzyme Inhibition, 2016)
A new series of 1-methyl-4-phenyl-6-substituted-3,4,6,7-tetrahydro-1H-pyrrolo[3,4- d]pyrimidine-2,5-diones (9a-h) were investigated as potential non-nucleoside anti-HCV, through Renilla luciferase (RL) assay using HuH-7-derived OR6 assay system. The target derivatives 9a-h were synthesized in moderate to good yields through nucleophilic substitution, followed by subsequent cyclocondensation of the 6-bromomethyl dihydropyrimidine derivative 8 with the appropriate primary amine. Biological screening revealed that compound 9a (EC50 of 28 μM) showed moderate anti-HCV activity; while compounds 9c, 9e and 9h showed weak activity.
Keywords: HCV inhibitors